Effect of the dose on the toxicokinetics of a quaternary mixture of rare earth elements administered to rats. (1st July 2021) - Jomaa, Malek; Dieme, Denis; Desrosiers, Mathieu; Côté, Jonathan; Fetoui, Hamadi; Pelletier, Guillaume; Nong, Andy; Bouchard, Michèle
Highlights: Toxicokinetics of cerium, praseodymium, neodymium and yttrium were similar. Kinetics of rare-earth elements (REEs) was influenced by the dose. Excretion of REEs in urine and feces decreased with increasing doses. Fraction of REE dose remaining in rat tissues at necropsy increased with dose. Shift in kinetics at high dose may result from higher retention in lysosomes. Abstract: Large human biomonitoring studies are starting to assess exposure to rare earth elements (REEs). Yet, there is a paucity of data on the toxicokinetics of these substances to help interpret biomonitoring data. The objective of the study was to document the effect of the administered dose on the toxicokinetics of REEs. Male Sprague-Dawley rats were injected intravenously with 0.3, 1 or 10 mg/kg body weight (bw) of praseodynium chloride (PrCl3 ), cerium chloride (CeCl3 ), neodymium chloride (NdCl3 ) and yttrium chloride (YCl3 ) administered together as a mixture. Serial blood samples were withdrawn up to 72 h following injection, and urine and feces were collected at predefined time intervals up to 7 days post-dosing. The REEs were measured by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). For a given REE dose, the time courses in blood, urine and feces were similar for all four REEs. However, the REE dose administered significantly impacted their kinetics, as lower cumulative excretion in urine and feces was associated with higher REE doses. The fraction of REE remaining in rat tissues at the terminal necropsy on post-dosing day 7 also increased with the dose administered, most notably in the lungs and spleen at the 10 mg/kg bw dose. The toxicokinetic parameters calculated from the blood concentration-time profiles further showed significant increases in the mean residence time (MRTIV ) for all four REEs at the 10 mg/kg bw dose. The shift in the REE kinetics at high dose may be explained by a higher retention in lysosomes, the main organelle responsible for accumulation of these REEs in different tissues.